2012
DOI: 10.1007/s10103-012-1222-0
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage of Er:YAG laser and dental bur prepared cavities in primary teeth restored with different adhesive restorative materials

Abstract: The purpose of this study was to evaluate and compare the effect of erbium:yttrium-aluminum-garnet (Er:YAG) laser irradiation and conventional dental bur cavity preparation on in vitro microleakage of class V cavities restored with different adhesive restorative materials and two types of self-etching adhesives in primary teeth. Standard class V cavities were prepared on 80 extracted primary, and the teeth were randomly divided into eight subgroups prepared either by dental bur or Er:YAG laser irradiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
3
25
0
2
Order By: Relevance
“…In agreement with this observation is a summation of the published literature 1,3,8,10,12,23,[27][28][29][30]32,37,38,44,45 . This agreement can be attributed to the more difficult and technically sensitive procedure involving adhesion to dentin 8 , as well as to the more complex and reduced inorganic content of the dentin compared to enamel 1 . An additional factor that could promote microgap formation on the dentinal margin is polymerization contraction that occurs at the strongest bonded surface of the cavity, which is the enamel margin 8 .…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In agreement with this observation is a summation of the published literature 1,3,8,10,12,23,[27][28][29][30]32,37,38,44,45 . This agreement can be attributed to the more difficult and technically sensitive procedure involving adhesion to dentin 8 , as well as to the more complex and reduced inorganic content of the dentin compared to enamel 1 . An additional factor that could promote microgap formation on the dentinal margin is polymerization contraction that occurs at the strongest bonded surface of the cavity, which is the enamel margin 8 .…”
Section: Discussionsupporting
confidence: 83%
“…The same results have been acquired by Baghalian et al for Clearfil S3 Bond; however they reported less microleakage when a two-step self-etch adhesive was used (Clearfil SE Bond) 1 . The more acidic nature (pH=2) and the dual hydrophobic primer-hydrophilic resin nature of the two-step adhesive improve marginal sealing and restrict micropenetration.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations